A catalog of the Chamaemyiidae of Chile (Diptera: Lauxanioidea) - Gaimari, Stephen D.; González, Christian R.; Elgueta, Mario (Zootaxa, 2024)
A catalog of the Chamaemyiidae of Chile is provided. We present all valid names and synonyms for the 14 species and eight genera and subgenera distributed in the country, including information about name, author, year of publication, page number, type-species, type depository, type locality and references. The chamaemyiid fauna of Chile is small, with the largest genus, Ortalidina Blanchard having only five species. Species of the subgenus Xenoleucopis Malloch of the genus Leucopis Meigen (even if referred to only as “sp.”) are the most cited due to their apparent potential as biological control agents, or the many works recording their biology. The geographical distribution of the different species was compiled from bibliographic data and revised collections.